189k views
4 votes
Solve 2(x - 3) = 5x - 1

User RafalK
by
6.2k points

2 Answers

4 votes

Answer:

-1 2/3 or -5/3 =x

Explanation:

First, begin by distributing the 2 throughout the parentheses of the left side of the equation.

2 times x is 2x, and 2 times 3 is 6. You are left with 2x - 6 on the left side.

Now, you have 2x - 6 = 5x - 1

Subtract 2x from both sides.

You get -6 = 3x - 1

Now, add 1 to both sides.

You are left with -5 = 3x

Finally, to isolate the variable x divided both sides of the equation by 3. You get -5/3, or in mixed number form, -1 2/3.

Hope this helps! Have a good day!

User Qiangks
by
5.8k points
2 votes

Answer:

X=-5/3

Explanation:

2X-6=5X-1

3X=-5

X=-5/3

User Sudhir Chauhan
by
5.8k points